Characterisation of blood microbiota in patients with liver cirrhosis. Issue 12 (December 2019) - Kajihara, Mikio; Koido, Shigeo; Kanai, Tomoya; Ito, Zensho; Matsumoto, Yoshihiro; Takakura, Kazuki; Saruta, Masayuki; Kato, Kumiko; Odamaki, Toshitaka; Xiao, Jin-zhong; Sato, Nobuhiro; Ohkusa, Toshifumi
Abstract : Background and aims: Bacterial infections arising in patients with liver cirrhosis are associated with life-threatening complications such as hepatic encephalopathy and spontaneous bacterial peritonitis in relation to bacterial translocation. To investigate the state of bacterial translocation, we surveyed the peripheral blood microbiota by 16S rRNA gene sequencing and analysed the blood microbial profiles. Methods: Sixty-six patients with liver cirrhosis were enrolled in this study, whereas 14 healthy individuals were also analysed as controls. Total RNA was purified from the peripheral blood, and an approximately 430 base pair genomic locus which included the V3-V4 region of the 16s rRNA gene was amplified and assessed using bacterial pyrosequencing. Results: At the genus level, a total of 183 operational taxonomic units were identified in cirrhotic patients, whereas 123 units in controls. Intergroup differences in gut microbiota were analysed by the linear discriminant analysis effect size, which showed that the abundance of Enterobacteriaceae was significantly higher in cirrhotics. On the contrary, the abundance of Akkermansia, Rikenellaceae and Erysipelotrichales were significantly lower in cirrhotics (relative abundance of Akkermansia in cirrhotics and controls: 0% and 0.2%, respectively; Rikenellaceae : 0.1% and 0.92%; Erysipelotrichales : 0.58% and 1.21%). Conclusion: The present study has demonstrated that various circulating bacteria are present in cirrhotic patients, and the diversity of such bacteria is consistent with the presence of dysbiosis in cirrhotics. Although the clinical significance of the findings remains to be clarified, the findings may potentially facilitate diagnostic and therapeutic attempts to comprehend and furthermore to manipulate bacterial infections in cirrhotic patients. Abstract : Supplemental Digital Content is available in the text.